1991
DOI: 10.3133/ofr91259a
|View full text |Cite
|
Sign up to set email alerts
|

Some geochemical features of the Blackbird and Jackass zones of the Yellowjacket Formation (middle Proterozoic) in east-central Idaho

Abstract: Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the U.S. Government. This report is preliminary and has not been reviewed for conformity with U.S. Geological Survey editorial standards nor with the North American stratigraphic codes. Although these data have been used by the U.S. Geological Survey and have been successfully imported into a number of data base and spreadsheet programs, no warranty, expressed or implied, is made by the USGS as to how su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…1, 2). (3) North of the Iron Lake fault and east of the Quartzite Mountain fault, the lower subunit of the Yellowjacket, as used by Connor and Evans (1986), Connor (1990a), and Evans and Connor (1993), is correlatable with the Apple Creek Formation (named by Anderson, 1961) in the northern part of the Lemhi Range (Connor, 1990a(Connor, , 1991. Mapping in the Lemhi Range (Tysdal, 1996a(Tysdal, , 1996bTysdal and Moye, 1996) revealed that the Apple Creek lies depositionally above the Big Creek Formation (named by Ruppel, 1975) and that no "type" Yellowjacket, Hoodoo, or unnamed post-Hoodoo strata are present.…”
Section: Revision Of Middle Proterozoic Yellowjacket Formation and Crmentioning
confidence: 99%
See 4 more Smart Citations
“…1, 2). (3) North of the Iron Lake fault and east of the Quartzite Mountain fault, the lower subunit of the Yellowjacket, as used by Connor and Evans (1986), Connor (1990a), and Evans and Connor (1993), is correlatable with the Apple Creek Formation (named by Anderson, 1961) in the northern part of the Lemhi Range (Connor, 1990a(Connor, , 1991. Mapping in the Lemhi Range (Tysdal, 1996a(Tysdal, , 1996bTysdal and Moye, 1996) revealed that the Apple Creek lies depositionally above the Big Creek Formation (named by Ruppel, 1975) and that no "type" Yellowjacket, Hoodoo, or unnamed post-Hoodoo strata are present.…”
Section: Revision Of Middle Proterozoic Yellowjacket Formation and Crmentioning
confidence: 99%
“…Strata directly above the Hoodoo remain unnamed. The most recent maps of the extensive area of the Salmon River Mountains directly north of the Iron Lake fault are those of Connor and Evans (1986), Connor (1990aConnor ( , 1991, and Evans and Connor (1993). These maps were completed prior to mapping and other studies in the northern part of the Lemhi Range (Tysdal, 1996a(Tysdal, , 1996b(Tysdal, , 1996c) that permit correlation and reconciliation of strata in the two mountain ranges.…”
Section: Revision Of Middle Proterozoic Yellowjacket Formation and Crmentioning
confidence: 99%
See 3 more Smart Citations